Employment quality index for the South African labour market. Issue 2 (3rd March 2020) - Yu, Derek
ABSTRACT: While the South African government specifically set targets on job creation in its numerous economic strategies since the economic transition, various local studies examined the levels and trends in labour force, employment and unemployment to evaluate if these targets were met. However, the quality of employment has not been thoroughly examined. This is the first local study that fills the existing research gap by deriving a composite, multidimensional employment quality index by taking 18 indicators from seven dimensions into consideration: wage, work hours and flexibility, employment security, income security, social benefits, skills and participation. Using the 2010–16 Quarterly Labour Force Survey data, the empirical findings indicated that highly educated, white male workers aged at least 35 years, who lived in urban areas of the Western Cape and Gauteng provinces, and were involved in high skilled occupations in the formal, public sector enjoyed significantly better employment quality.